Norma i „wolność" formy sonetowej oraz „ryzyko wolności". (Przykład twórczości kilku poetów współczesnych - belgijskich i polskich) - Lubas-Bartoszyńska, Regina (Wydawnictwo Naukowe UAM, 2005)
Taking into account a few sonnets by two of the twentieth-century Belgian poets and four Polish ones, this paper aims to examine the accomplishment of the sonnets and the freedom of such accomplishment, which is typical of normativism: normativism which increases the risk of classifying this poetic form as sonnet. Reflecting on the greatness of the risk involved in writing this type of poetry in the twentieth century results in distinguishing three levels of the risk: the risk of interpreting the sonnet as a fixed poetic form in view of the pervasiveness of free verse taken as parody, the risk of the second level operating within the genre (breaking the rules of the literary genre), and the risk of the third and deepest level - imbuing the lyric form with extra-poetic and extra-literary elements. The choice of the Polish works was based on the fact that metatextual reflection is to be found there, which generalizes the theoretical meaning of these three levels through the use of metaphorical language.
Norm and "freedom" of the sonnet form and "the risk of freedom". (An example of works of several poets - Belgian and Polish)